EXERCISE STRETCHING AS AN INTERVENTION TO PREVENT BACK PAIN IN HOME INDUSTRY SHOES KAB. GARUT: A CASE REPORT - Akmal Sybromiilsy; Dadang Purnama; Adelse Prima Mulya; Witdiawati (Indonesian Journal of Community Health Nursing, 2025)
Introduction: Working positions that are not in accordance with the principles of body ergonomics will cause work-related illnesses, namely complaints of back pain. Risk factors that can trigger discomfort in the back area include age, body mass index, length of work, type of work chair, sitting position, and physical activity performed. Stretching exercises can increase muscle blood circulation causing spasm and reduced ischemia so that the metabolism of materials needed by the body becomes well dispersed and processes the elimination of waste materials that are not needed by the body more efficiently The purpose of this study is to increase knowledge about how to deal with back pain in workers. Method: This type of research used a qualitative study method with a total sample of 8 male workers, all workers did not know about ergonomic positions and there were 6 workers who experienced complaints of back pain. Result:Actions that can be used to increase knowledge and reduce pain levels in workers withproviding health education on ergonomic positions and stretching exercises. Conclusion:Based on these actions, workers already know and understand about ergonomic positions that can be applied in the workplace and after doing 12 stretching exercises the workers stated that being more relaxed and comfortable between work, the felt back pain also reduced, to a scale of 2 . Keywords: Back Pain, Stretching Exercises, Worker